Robotic surgery and malpractice - USLUOĞULLARI, FATİH HİTAMİ; TIPLAMAZ, SITKI (AVES, 2017)
Robotic surgery has undergone exponential growth since the last two decades. Employment of new technologies in surgery creates many ethical challenges concerning the advantages and disadvantages different from conventional surgery, ensuring safety of the new technology, giving permission to surgeons for using new technology, the way of informing patients before undergoing a new technology or technique, and the responsibilities of surgeons, firms and hospitals to the patients etc. In this review, robotic surgery was discussed from malpractice perspective.
Keywords: Competency; malpractice; robotic surgery; ETHICAL-ISSUES